Could cold plasma act synergistically with allogeneic mesenchymal stem cells to improve wound skin regeneration in a large size animal model?. (May 2021) - Melotti, Luca; Martinello, Tiziana; Perazzi, Anna; Martines, Emilio; Zuin, Matteo; Modenese, Daniela; Cordaro, Luigi; Ferro, Silvia; Maccatrozzo, Lisa; Iacopetti, Ilaria; Patruno, Marco
Abstract: Skin wound healing may sometimes lead to open sores that persist for long periods and expensive hospitalization is needed. Among different kinds of therapeutic innovative approaches, mesenchymal stem cells (MSCs) and low-temperature atmospheric pressure cold plasma (ionized gas) have been recently tested to improve this regenerative process. To optimize wound healing the present study intended to combine, for the first time, these two novel approaches in a large size animal wound healing model with the aim of assessing the putative dual beneficial effects. Based on clinical, histopathological, and molecular results a synergistic action in a second intention healing wound in sheep has been observed. Experimental wounds treated with cold plasma and MSCs showed a slower but more effective healing compared to the single treatment, as observed in previous studies. The combined treatment improved the correct development of skin appendages and structural proteins of the dermis showing the potential of the dual combination as a safe and effective tool for skin regeneration in the veterinary clinical field. Highlights: Wounds treated with cold plasma and MSCs showed a high-quality standard of healing. The combined treatment improved the correct development of skin appendages. The improved angiogenesis supported the maturation of proper granulation tissue.